PERSEPSI MAYARAKAT TENTANG MUNCULNYA PENGEMIS DI MASA PANDEMI COVID 19 DI KOTA TEMBILAHAN - Yuli Asmarita; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Beggars in the Batang Tuaka Tembilahan City traffic light area are considered to be a lot of disturbing to the community, namely the people who are around the traffic lights themselves. The beggars around the traffic lights are quite disturbing to the surrounding community, not many of them ask for money forcibly and do not move quickly before being given money, this makes people very disturbed by the presence of beggars who force to be given money. The treatment of beggars like that makes you feel uncomfortable when you are in the traffic light environment. In the current pandemic, there are many beggars roaming around the traffic lights, unlike during the non-pandemic, there are only a few beggars and they don't bother the community too much. Various reasons given by beggars when asked why they beg, not infrequently they are children who drop out of school and choose to beg in order to still earn money. The treatment of beggars like that makes you feel uncomfortable when you are in the red light environment. In the current pandemic mass, there are many beggars hanging around the traffic lights, unlike when it was not a pandemic, there were only a few beggars and they didn't bother the community too much. Various reasons were given by beggars when asked why they were begging, not infrequently they were children who dropped out of school and chose to beg in order to still earn money. The research was conducted to find out: 1) Public perception of beggars, 2) What are the factors that influence public perception of beggars, who are in the traffic light area of Batang Tuaka Tembilahan City. The method used in this study is a quantitative method with a descriptive approach. The results of the research obtained are: 1) Perception of the people who are in the traffic light area of Batang Tuaka Tembilahan City. Most of the community admitted that they were disturbed by the presence of beggars at this time. 2) There are two factors that influence people's perceptions of beggars, namely positive perceptions and negative perceptions, positive perceptions describe someone who can accept and support the perceived object, while negative perception describes someone who opposes or rejects the perceived object. Keywords: Perception, Society, Beggars